2019
DOI: 10.1111/ffe.13154
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity effects on mixed‐mode I/II stress intensity factors and fracture path of laboratory asphalt mixtures in the shape of SCB specimen

Abstract: Edge cracked semi-circular shape specimen subjected to three point bend loading is a favourite test specimen for determining fracture toughness of asphalt mixtures. However, in the vast majority of previous experimental works, the homogeneous medium assumption has been considered for determining the stress intensity factor and geometry factors of asphalt mixtures tested with this test configuration. As a more realistic model and in order to consider the effects of heterogeneity on corresponding values of stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…A possible reason for this observation can be related to the decreasing in the viscosity and increasing the stiffness of bitumen material at subzero temperatures, which results in increasing the stiffness of whole HMA mixture at low testing temperatures. Furthermore, according to some analyses available in the literature, the SIF becomes more by increasing the stiffness or elastic modulus of bitumen used in the composition of two‐phase aggregate/mastic composite structure 52,53 . As it is well understood and has been reported in previous papers, 8,9,12,13,31,54–58 the asphalt binder as a viscoelastic material becomes more stiff at subzero temperatures up to the lower PG limit of the bitumen that is related to the glass temperature of binder material.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A possible reason for this observation can be related to the decreasing in the viscosity and increasing the stiffness of bitumen material at subzero temperatures, which results in increasing the stiffness of whole HMA mixture at low testing temperatures. Furthermore, according to some analyses available in the literature, the SIF becomes more by increasing the stiffness or elastic modulus of bitumen used in the composition of two‐phase aggregate/mastic composite structure 52,53 . As it is well understood and has been reported in previous papers, 8,9,12,13,31,54–58 the asphalt binder as a viscoelastic material becomes more stiff at subzero temperatures up to the lower PG limit of the bitumen that is related to the glass temperature of binder material.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, according to some analyses available in the literature, the SIF becomes more by increasing the stiffness or elastic modulus of bitumen used in the composition of two-phase aggregate/mastic composite structure. 52,53 As it is well understood and has been reported in previous papers, 8,9,12,13,31,[54][55][56][57][58] the asphalt binder as a viscoelastic material becomes more stiff at subzero temperatures up to the lower PG limit of the bitumen that is related to the glass temperature of binder material. Hence, for the bitumen material used in the current research with PG , it is expected to observe an enhancement on the overall strength and load carrying capacity of binder and consequently the whole asphalt mixture.…”
Section: Resultsmentioning
confidence: 95%
“…But for the sake of simplicity, we assumed circular shape for the geometry of distributed aggregates inside the texture of heterogeneous HMA overlay. However, the authors were investigated in their previous works the influence of aggregate shape on the fracture parameters 34 . They examined different shapes such as hexagonal, diagonal, square, and circular configurations for the aggregates distributed inside the mixture of asphalt concrete and concluded that the SIFs and the T ‐stress values are not affected noticeably by the shape of aggregates.…”
Section: Results and Disscussionmentioning
confidence: 99%
“… Ai0.25emmin0.25em0.25emj=1NiAij0.25em0.25emAi0.25emmax, where A i min and A i max are minimum and maximum summation area of aggregates, respectively, in group i which is determined based on the asphalt mixture aggregate gradation and A ij is the area of aggregate j in group i . More details about this algorithm can be found in the work by Aliha et al 34 The aggregate gradation No. 4 (according to the Iranian Paving Standard Code‐234 42 ) was considered for running the AGP algorithm.…”
Section: Agp Algorithmmentioning
confidence: 99%
See 1 more Smart Citation